M3Y-P0 as a Residual Interaction to Study Elastic Magnetic Electron Scattering Form Factors for Ca-41 - Majeed, Firas Z (Al-Nahrain Journal of Science, 2018)
The studying of elastic magnetic electron scattering form factors has been done for Ca-41with the consideration of 1f7/2 orbit as a model space and F7MBZ as a model space effective interaction to construct the model space wave functions. Core and higher configurations orbits have been included to the calculations as a first order corrections through the so called core polarization effect with the use of M3Y-P0 as a residual interaction to join the particle hole pair across the model space with 2 ħω excitation energy, with the available experimental data, theoretical results have been compared with it.